Guideline-based management of male infertility: Why do we need it? - Landon W Trost; Ajay Nehra (Indian Journal of Urology, 2011)
The current clinical guidelines for the management of infertility as presented by the American Urologic Association and European Association of Urology represent consensus opinions for the management of male-factor infertility. The goal of the present study is to define the currently available guidelines for male-factor infertility, provide a rationale for why guidelines should be implemented, and review concerns and shortcomings towards their incorporation into clinical practice. Successfully integrating guidelines into clinical practice offers the potential benefit of creating a standardized, efficient, and cost-effective algorithm for the evaluation of infertility and facilitates future research. Despite their availability and ease of use, many clinicians fail to adopt clinical guidelines for numerous reasons including decreased awareness of available guidelines, insufficient time, lack of interest, and personal financial considerations. The current guidelines are limited by the inability to generalize recommendations to a heterogeneous patient sample, the lack of interdisciplinary adoption of guidelines, and the need for additional emphasis on prevention and lifestyle modifications. Future direction for the current guidelines will likely incorporate a multidisciplinary approach with increasing utilization of genetic analysis and novel treatment strategies. As the field of infertility continues to expand, the utility of guidelines combined with physician clinical judgment will remain prominent in the treatment of male-factor infertility.